2019
DOI: 10.12688/wellcomeopenres.15147.2
|View full text |Cite
|
Sign up to set email alerts
|

Expert quotes and exaggeration in health news: a retrospective quantitative content analysis

Abstract: BackgroundThis research is an investigation into the role of expert quotes in health news, specifically whether news articles containing a quote from an independent expert are less often exaggerated than articles without such a quote.MethodsRetrospective quantitative content analysis of journal articles, press releases, and associated news articles was performed. The investigated sample are press releases on peer-reviewed health research and the associated research articles and news stories. Our sample consist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…There also is some evidence that health news stories which include external comments tend to feature less hyperbole. Bossema et al found: "the relative odds that an article without an external expert quote contains an exaggeration of causality is 2.6" [29]. While observational in nature, this study still suggests an argument to give reporters more time to find a diversity of opinions.…”
Section: How Good (Or Bad) Is Today's Health Care Journalism?mentioning
confidence: 55%
“…There also is some evidence that health news stories which include external comments tend to feature less hyperbole. Bossema et al found: "the relative odds that an article without an external expert quote contains an exaggeration of causality is 2.6" [29]. While observational in nature, this study still suggests an argument to give reporters more time to find a diversity of opinions.…”
Section: How Good (Or Bad) Is Today's Health Care Journalism?mentioning
confidence: 55%
“…A large majority of UK and Dutch news articles discussing peer-reviewed health-related research included quotes from the original study authors but only 7.5 and 7.0% respectively contained a 'new quote' from an expert source not included in press release. 82 Our study had far larger representation from the Deputy and Chief CMOs (32%) and HIQA researchers (37%) in the media coverage. The inclusion of the external 'expert quotes' may have been a contributing factor into why the reporting of key messages were largely accurate and generally did not exaggerate the causality of findings.…”
Section: International Journal Of Health Policy and Management (Ijhpm)mentioning
confidence: 79%
“…The inclusion of the external ‘expert quotes’ may have been a contributing factor into why the reporting of key messages were largely accurate and generally did not exaggerate the causality of findings. 82 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But they may also be used to discuss topics unrelated to their fields of expertise” (Merkley, 2020, p. 531). Adding expert sources to a news story can help journalists evoke a rhetoric of authority and add a critical perspective to the narrative (Bossema et al, 2019). The pressure of the deadline also affects the choice of expert sources, leaving journalists with a preference for sources who can promptly and reliably answer interview requests (Peters, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%